Letter to Jess Unruh from Jane Tolmach and Adele Leopold - Jane Tolmach::::::; Adele Leopold:::::: (1971)
In this January 1, 1971 letter, Jane Tolmach and Adele Leopold invite Jess Unruh to speak at the Key Women Award Party on January 16, 1971, at the Beverly Hilton in Los Angeles. The event honors women volunteers who supported Democratic nominees in the 1970 campaign, and Unruh is especially encouraged to attend because of the importance of his campaign. They express hope that he and Virginia will join them in recognizing these dedicated campaign workers and send best wishes for the new year.